Promotion of healthy eating patterns among employees of a primary health care unit - Paula Martins Horta; Luana Caroline dos Santos; Roseli Gomes de Andrade (O Mundo da Saúde)
Non-transmissible chronic diseases and inadequate eating practices are also seen among health professionals. In this context, the present study aimed to promote healthy eating patterns among employees (n = 42) of a primary healthcare unit from Belo Horizonte-MG. First, a structured interview was done in order to characterize health and nutritional profile of subjects. After that, an intervention program started which lasted six weeks. Six weekly activities relating to food and nutrition education were carried out and their themes were: food groups and healthy eating; physical activity practice and adequate water ingestion; milk and dairy and the importance of calcium; fruits and the importance of using whole foods; nutritional labeling, whole grains and diet vs. light; sodium consumption and aromatic herbs. Posters and murals were presented, food degustation was promoted, folders were given and giveaways promoted. A non-identified self-applied questionnaire was used to evaluate the acceptance by participants of interventions. Most participants were adults (90.3%), women (74.2%) and nursing auxiliaries (29.0%). Overweight was seen in 38.8% of workers in addition to a high frequency of fried food and sweets consumption. After intervention, 100% of all employees evaluated (n = 21) considered their participation in the study successful and referred interest in its continuation. It was also identified that 61.9% of the employees had already done some recipe worked, and the score of knowledge application to daily life reached 8.3 (1.1). The study pointed out a different way for promoting healthy eating patterns for health professionals.